Characterization of Imprinted Genes in Rice Reveals Conservation of Regulation and Imprinting with Other Plant Species - Chen, Chen (Plant Physiol, 2018)
Genomic imprinting is an epigenetic phenomenon by which certain genes display differential expression in a parent-of-origin-dependent manner. Hundreds of imprinted genes have been identified from several plant species. Here, we identified, with a high level of confidence, 208 imprinted gene candidates from rice (Oryza sativa). Imprinted genes of rice showed limited association with the transposable elements, which contrasts with findings from Arabidopsis (Arabidopsis thaliana). Generally, imprinting in rice is conserved within a species, but intraspecific variation also was detected. The imprinted rice genes do not show signatures of selection, which suggests that domestication has had a limited evolutionary consequence on genomic imprinting. Although conservation of imprinting in plants is limited, we show that some loci are imprinted in several different species. Moreover, our results suggest that different types of epigenetic regulation can be established either before or after fertilization. Imprinted 24-nucleotide small RNAs and their neighboring genes tend to express alleles from different parents. This association was not observed between 21-nucleotide small RNAs and their neighboring genes. Together, our findings suggest that the regulation of imprinting can be diverse, and genomic imprinting has evolutionary and biological significance.